PENGARUH KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL INTERVENING (Studi pada RSUD Tugurejo Semarang) - Kristianto, Dian (JURNAL BISNIS STRATEGI, 2011)
Previous researches have shown controversial result about job satisfaction to organizational commitment relationship, and job satisfaction and organizational commitment to job performance relationship.  The purpose of this study is to examine the relationship between job satisfaction, organizational commitment, and job performance of nurses in RSUD Tugurejo Semarang. The questionnaires were sent to 130 nurses. Path analysis revealed positive relationship existed between the dependent variables and the independent variables. Moreover, organizational com- mitment mediates the relationship between job satisfaction and job performance. Based on total R2 determination, model in this study can be accepted.This study has several limitations. First, the data collected in public hospital; therefore, its results cannot be generalized. Second, difficulty in collecting  some data. Third, there was a great rotation on all sectors in this hospital that could affect the respondent’s answers. Future research may be directed to other objective measurement and use broader object.